Determining the Pillars in a Framework of Mobile Application for Kindergarten Early Reading - Mohamad, Abdul Jalil; Lakulu, Modi; Samsudin, Khairulanuar (Journal of Informatics and Mathematical Sciences, 2017)
Many children around the world faced reading difficulties problem. In order to overcome this obstacle, many program and initiative has been proposed and implemented. Mobile application seem have a great potential to enhance reading skills acquisition among young children. However, research exposed many of existing mobile application for young children lack of the criteria for well-design learning tool for early childhood. The disadvantage of these application due to there a lack of specific framework for this niche area. Against to this urgency, researchers focused on formulation a framework of mobile for kindergarten early reading. This research aimed to determine the pillars in a framework of mobile application for kindergarten early reading based on the consensus of expert using Fuzzy Delphi Method. Result indicated a highly consensus on three proposed pillars; technology, pedagogy and content.